ابتكار تعليم اللغة العربية في العصر الرقمي: لتحسين وسائل التواصل الاجتماعي (يوتيوب وفيسبوك وإنستغرام وتيك توك) كوسيلة تعليمية - febri, Febrina Dwi (An Nazhair: Journal of Arabic Education, 2025)
Arabic, as part of classical intellectual heritage, continues to show dynamic development, especially within the context of contemporary education that is increasingly integrated with digital technology. This research aims to analyze the utilization of social media platforms, including YouTube, Facebook, Instagram, and TikTok, as effective and relevant media for Arabic language learning in the digital era. This study, using a descriptive qualitative approach based on a literature review, explores the effectiveness of various platforms in improving students' language proficiency. Findings indicate that YouTube plays a significant role in developing listening skills and understanding language structures through systematic and varied educational video content. Facebook supports the creation of a collaborative learning ecosystem and strengthens writing and discussion skills in Arabic. Instagram is considered capable of introducing basic vocabulary and expressions visually through images and interactive features such as Stories,reels and live broadcasts. Meanwhile, TikTok presents a learning approach that is short, engaging, and contextual, thereby increasing students' enthusiasm and motivation to learn. However, there are several obstacles hindering the optimization of social media in learning, including low digital literacy, unequal access to technology, the dominance of non-educational content, and a lack of selection of appropriate learning materials. Therefore, enhancing educators' digital capacity, selecting content that supports pedagogical goals, and designing adaptive learning strategies are key factors in making social media a relevant, creative, and contextual tool for Arabic language learning in the digital era.